The Religious Dimension of Hong Kong's Umbrella Movement - Ng, Nancy (A journal of church and state, 2018)
The preceding statements by Chris Buckley and Austin Ramzy and by Phil Entwistle are indicative of the highly diverging viewpoints about the organizational natu